2008
DOI: 10.1017/s1931436100000523
|View full text |Cite
|
Sign up to set email alerts
|

Do More Expensive Wines Taste Better? Evidence from a Large Sample of Blind Tastings

Abstract: Individuals who are unaware of the price do not derive more enjoyment from more expensive wine. In a sample of more than 6,000 blind tastings, we …nd that the correlation between price and overall rating is small and negative, suggesting that individuals on average enjoy more expensive wines slightly less. For individuals with wine training, however, we …nd indications of a positive relationship between price and enjoyment. Our results are robust to the inclusion of individual …xed e¤ects, and are not driven b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(18 citation statements)
references
References 14 publications
1
15
0
2
Order By: Relevance
“…Conversely, the beer sample remained valued at a similar price point, likely due to the incongruence between sample and context, with panelists not freely associating beer with the winery context. Studies have previously demonstrated that price can influence the perceived quality or taste of a food or beverage [48]. Indeed, in our study, the Pearson’s correlation coefficient between liking and willingness to pay was 0.520 ( p < 0.001).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Conversely, the beer sample remained valued at a similar price point, likely due to the incongruence between sample and context, with panelists not freely associating beer with the winery context. Studies have previously demonstrated that price can influence the perceived quality or taste of a food or beverage [48]. Indeed, in our study, the Pearson’s correlation coefficient between liking and willingness to pay was 0.520 ( p < 0.001).…”
Section: Discussionsupporting
confidence: 51%
“…Consumers typically associate more expensively priced products as being higher in quality, and this expectation directly influences sensory judgments. Even sommeliers, who are classically trained in wine, assume that higher priced wines are better and, as such, may alter their hedonic ratings accordingly [48]. Consumers’ impressions that the beer was more appropriate for the bar and that the champagne was more appropriate for the winery suggests that there are indeed schemas that guide our understanding of where a food or beverage should be consumed.…”
Section: Discussionmentioning
confidence: 99%
“…Wine is a product category with a wide product range, not only in specialised wine stores but also in grocery stores. This is the result of the high number of wine producers in various countries and regions as well as diverse consumer preferences regarding quality and taste (Goldstein et al, 2008;Barreiro-Hurlé et al, 2008). Wine quality and taste are influenced by numerous factors, e.g.…”
Section: State Of the Art And Hypothesesmentioning
confidence: 99%
“…In the wine literature, there is generally consensus that 'price' and 'origin' are among the most important extrinsic product attributes for consumers. 'Price' is relevant for consumers not only because of its economic effect but also because of its role as an important quality cue, in that consumers generally assume that more expensive wines are of higher quality than cheaper wines (Lockshin et al, 2006;Goldstein et al, 2008).…”
Section: State Of the Art And Hypothesesmentioning
confidence: 99%
“…In general, food preference depends, among others, on the symbolic value that the food product has for a consumer; if the product is perceived as valuable or rare, the consumer may even perceive a more favorable taste as they consume it [47]. For adults, one well-known case is that of upscale wines, which may be perceived as tasting better only because of their price and not the real feeling of taste [48]. A similar association may be assumed for children from lower socioeconomic status families, which may perceive rarely consumed products as tastier compared to perception of other children.…”
Section: Discussionmentioning
confidence: 99%